Personality determinants of the quality of religious experiences - Głaz, Stanisław (Studia Psychologica: Theoria et praxis, 2003)
A group of 200 students (22-25 years old) from Cracow were examined. Two groups of men and two groups of women of high and low intensity of religious experience – the presence and the absence of God – were taken into account to make the results of the research clearer. The author of the article, interested in the issue of religious experience, made an attempt to present the personality features which characterise persons of high and low intensity of experience of God in their lives. The results show that not always and not all people of high intensity of experience of God are characterised by all the features of welldeveloped and mature personality.